Strategi guru TPQ dalam peningkatan bahasa arab anak-anak di TPQ Nurul Ihsan Gresik - Nisa’, Ismi Khoirun (Maliki Interdisciplinary Journal, 2025)
Mastery of the Arabic language at TPQ Nurul Ihsan is crucial for children to understand the Qur’an and other religious texts, yet it faces various challenges. This study aims to identify and evaluate Arabic learning strategies applied by teachers at this TPQ, focusing on the effectiveness of teaching methods, parental involvement, and the use of interactive learning media. The methods used in this research include direct observation and interviews with teachers. The results indicate that a combination of communicative methods, a direct approach, and the use of interactive media, such as videos and Arabic songs, successfully increased children’s motivation and proficiency in Arabic. The communicative method proved effective in improving speaking skills, while the direct approach strengthened grammar and vocabulary understanding. Interactive media made the learning process more engaging for children and boosted their motivation. This study is expected to provide valuable insights for other TPQs in developing more adaptive and innovative Arabic teaching strategies, as well as encouraging parental involvement in the learning process at home.